Using IMU sensors to compare rowing ergometers with rowing on the water - Knarr, C.; Kwoun, H.; Kleshnev, V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
Indoor rowing ergometers serve as tools to refine stroke technique, improve stamina, and allow training regardless of weather conditions. Currently, the most widely utilized models are the Concept 2 (C2) and the Rowperfect 3 (RP3) static and dynamic ergometers. The timing and magnitude of acceleration during different phases of the rowing stroke have been shown to play a crucial role in performance. Current methods used to extract individual rowing strokes are difficult to apply and utilize complicated measurements, such as oar angle, filters, or machine learning. This paper compares the rowing acceleration profile across three rowing training devices. The C2 and RP3 ergometer handle and seat accelerations are compared to those of a single scull shell using a peak detection signal processing technique. This technique easily identifies peaks during a rowing session so that individual strokes can be extracted. Inertial measurement units (IMU) were attached to the oar handle and the ergometer seat/cage and the scull to measure the acceleration profile of individual strokes. The ergometer drag factor was adjusted to match the boat`s drag factor. One Division I male athlete rowed for 90 s, with 60 s of steady state rowing at 20 strokes/min (spm). The mean difference in acceleration between each ergometer and the boat was calculated. Findings suggest the RP3 ergometer acceleration profile more closely matches that of on-water rowing. Our analysis illuminates key differences between ergometers and on-water rowing, which can help rowers understand how their ergometer training translates to on-water rowing.